Development and characterization of an automated system for generation and collection of cigarette smoke (ASGCS) for rapid and accurate exposure and toxicity assessment - Young-Ji An; Sung-Hwan Kim; Moonjung Hyun; Yong-Hyun Kim (Ecotoxicology and Environmental Safety)
Whole cigarette smoke condensate (WCSC) is a crucial tool for assessing tobacco product toxicity, offering advantages in storage, transportation, and concentration control. However, the lack of an automated system for WCSC production poses challenges in ensuring batch-to-batch consistency and test article reproducibility, both of which are essential for reliable toxicity evaluation. In this study, we developed and characterized an automated system for the generation and collection of cigarette smoke (ASGCS) to efficiently produce WCSC. Under Health Canada Intense smoking conditions, the ASGCS achieved a low smoke leakage rate of 9.45 ± 0.47 %, facilitating the collection of total particulate matter (TPM) at a relatively high concentration of 21.2 ± 0.2 mg cig–1. Nicotine and total volatile organic compound concentrations in WCSC prepared using the ASGCS were 1.25 ± 0.01 μg cig–1 and 2276 μg cig–1, corresponding to transfer rates of approximately 65 % and 135 % relative to cigarette smoke, respectively. WCSC exposure demonstrated a dose-dependent decrease in cell viability, with an IC50 of 0.26 mg mL–1 (R2 = 0.9171). These findings confirm the physical performance of ASGCS and the chemical and biological reliability of WCSC produced using this system. The ASGCS offers a robust platform for the rapid and accurate assessment of tobacco product toxicity.